2020
DOI: 10.1002/dta.2821
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and subjective effects of 1P‐LSD in humans after oral and intravenous administration

Abstract: 1‐Propanoyl‐lysergic acid diethylamide (1P‐LSD) appeared as a non‐controlled alternative to LSD a few years ago. Although evidence is beginning to emerge from in vitro and animal studies that 1P‐LSD might serve as a prodrug for LSD, an equivalent evaluation in humans is unavailable. Controlled oral and intravenous self‐administrations of 100 μg 1P‐LSD hemitartrate are reported in two human volunteers followed by analyses of urine and serum samples using a fully validated LC–MS/MS method. Psychometric evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Looking to their pharmacology, each is seemingly prodrugs of their respective progenitor’s psilocybin and LSD, and is reported to produce comparable effects to their predecessors (Coney et al 2017 ; Palamar and Acosta 2020 ). 4-AcO-DMT ( O -Acetylpsilocin) is an acetylated equivalent of psilocybin’s primary bioactive metabolite psilocin (Madsen et al 2019 ) previously suggested to be a suitable substitute for psilocybin for clinical use (Nichols 1999 ), with 1P-LSD (1-Propionyl-d-lysergic acid diethylamide) similarly hydrolysed to LSD upon intake (Brandt et al 2016 ; Grumann et al 2020 ). These findings may extend to other closely related homologues such as 4-HO-MET or ALD-52, albeit with variable potency.…”
Section: Discussionmentioning
confidence: 99%
“…Looking to their pharmacology, each is seemingly prodrugs of their respective progenitor’s psilocybin and LSD, and is reported to produce comparable effects to their predecessors (Coney et al 2017 ; Palamar and Acosta 2020 ). 4-AcO-DMT ( O -Acetylpsilocin) is an acetylated equivalent of psilocybin’s primary bioactive metabolite psilocin (Madsen et al 2019 ) previously suggested to be a suitable substitute for psilocybin for clinical use (Nichols 1999 ), with 1P-LSD (1-Propionyl-d-lysergic acid diethylamide) similarly hydrolysed to LSD upon intake (Brandt et al 2016 ; Grumann et al 2020 ). These findings may extend to other closely related homologues such as 4-HO-MET or ALD-52, albeit with variable potency.…”
Section: Discussionmentioning
confidence: 99%
“…Friederike Holze 1, † , Matthias E. Liechti 1, * , † , Nadia R.P.W. Hutten 2 , Natasha L. Mason 2 , Patrick C. Dolder 2 , Eef L. Theunissen 2 , Urs Duthaler 1 , Amanda Feilding 3 , Johannes G. Ramaekers 2 and Kim P.C. Kuypers 2 "Microdoses" of lysergic acid diethylamide (LSD) are used recreationally to enhance mood and cognition.…”
Section: Pharmacokinetics and Pharmacodynamics Of Lysergic Acid Diethmentioning
confidence: 99%
“…Lysergic acid diethylamide (LSD) is a well‐known classic serotonergic psychedelic that is widely used for recreational purposes 1 . LSD is well‐absorbed, 2,3 and maximal LSD concentrations are reached 1.5–2 hours after oral administration 4 . LSD is mainly metabolized to inactive O‐H‐LSD, which is renally eliminated 3 .…”
mentioning
confidence: 99%
“…Similar to ALD-52, 1P-LSD and 1B-LSD undergo hydrolysis to LSD in vitro. 9 Studies in rats 8 and humans 15 have confirmed that 1P-LSD is hydrolyzed to LSD in vivo.…”
mentioning
confidence: 93%